Authoring of interventions with on-demand generation of screen for mobile devices - Cunha, Bruna C.R.; Rodrigues, Kamila R.H.; Scalco, Leonardo F.; Zaine, Isabela; Viel, Caio C.; Pimentel, Maria da Graça C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2018)
In this paper we present the ESPIM system, a set of tools that enables the authoring of intervention programs with focus on health and education. Created programs are played in a mobile app that generates screens on demand, according to their definition provided by JSON fi les. Using state-of-art technology we aim to provide a platform that can be used by professionals of health and education with no programming skills. To achieve that the system presents an intuitive authoring interface, built with requirements obtained with experts in diff erent areas and with continuous feedback from evaluations, and a friendly mobile app, which presents elementsthat users are familiar and a good aesthetic design to motivate them. The system is being successfully used by professionals in health-related areas and shows many advantages in comparison tosimilar platforms.